Who Authored On Liberty? Stylometric Evidence on Harriet Taylor Mill's Contribution. Issue 2 (June 2022) - Schmidt-Petri, Christoph; Schefczyk, Michael; Osburg, Lilly
Abstract: It is well known that John Stuart Mill (JSM) repeatedly acknowledges Harriet Taylor Mill's (HTM) substantial contribution to On Liberty . After her death, however, he decides to publish the book under his name only. Are we justified in continuing this practice, initiated by JSM, of refusing unequivocal co-authorship status to HTM? Drawing on stylometric analyses, we make a preliminary case that JSM did not write On Liberty all by himself and that HTM had a hand in formulating it. Drawing on plausible standards for authorship ascription, we further point out that authorship status requires, in addition to a substantial contribution, the approval by all contributors. We discuss potential reasons to assume that HTM did not approve the published version of On Liberty and would have objected to including her name on the title page.